Evasive plankton: Size‐independent particle capture by ascidians. Issue 4 (8th January 2021) - Jacobi, Yuval; Shenkar, Noa; Ward, J. Evan; Rosa, Maria; Ramon, Guy Z.; Shavit, Uri; Yahel, Gitai
Abstract: Direct measurements of the capture efficiency of planktonic cells by seven solitary ascidians were made in situ and in the laboratory and compared with the capture efficiency of polystyrene microspheres. The capture efficiency of the microspheres was significantly higher than that of planktonic cells over the entire tested size range (0.3–15  μ m). Submicron polystyrene spheres with a surface modification consisting of an adsorbed layer of a nonionic, long‐chain surfactant were removed at lower efficiencies than uncoated particles whereas for larger microspheres (1–3 μ m), the coating had no effect. Our findings strengthen the concept that some planktonic cells evade capture by mucus‐based suspension feeders, and that evasion happens throughout the pico‐ and nanoplankton size range. Thus, the common assumption that particles larger than ~ 1 μ m are always captured at a 100% efficiency by ascidians should be reconsidered. Some large microalgae cells (> 3–12  μ m) were captured at a lower efficiency than the largest microspheres used (3 μ m) suggesting that other factors, such as surface interactions and particle shape, play an important role in capture throughout the tested size range. Furthermore, given the lack of a known active selection mechanism in ascidians, we propose that some plankton possess traits that allow them to evade predation by mucus‐based suspension feeders.